Mechanisms of Nephrotoxic Action of Immunodepressants, Calcineurine Inhibitors - A. V. Nikitin (Антибиотики и Химиотерапия)
The use of immunodepressants in the medical practice provided tens of thousands of favourable outcomes of the liver, kidney or heart transplantation and significant success in the treatment of a number of autoimmune diseases. Calcineurine inhibitors (cyclosporine A and tacrolimus) provoke a number of adverse reactions. Among them nephrotoxicity is clinically most dangerous. Complex estimation of the immunological and biochemical indices in the treatment with calcineurine inhibitors is an important precondition for increasing the efficacy of immunodepressive therapy and decreasing the frequency and level of the adverse reactions.